2012
DOI: 10.1167/iovs.12-9832
|View full text |Cite
|
Sign up to set email alerts
|

Decreased microRNA-155 Expression in Ocular Behcet's Disease but Not in Vogt Koyanagi Harada Syndrome

Abstract: The present results suggest that miR-155 expression is decreased in active BD but not in VKH patients. Downregulated miR-155 may be involved in BD pathogenesis by targeting TAB2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 37 publications
3
64
0
5
Order By: Relevance
“…17 The supernatants were harvested for IL-17 ELISA. The cells were collected for flow cytometry analysis.…”
Section: Dc-cd4mentioning
confidence: 99%
“…17 The supernatants were harvested for IL-17 ELISA. The cells were collected for flow cytometry analysis.…”
Section: Dc-cd4mentioning
confidence: 99%
“…Kaneko et al [49] reported that no microRNA was significantly overexpressed in sympathetic Characterization of microRNA expression profiling in peripheral… ophthalmia, a bilateral diffuse granulomatous uveitis of both eyes following trauma to one eye, whereas 27 miRNAs were markedly downregulated, suggesting that downregulated miRNAs may play a crucial role in the pathogenesis of sympathetic ophthalmia. Zhou et al [50] also reported that only miR-155 expression was significantly decreased in peripheral blood mononuclear cells and dendritic cells from Behcet's disease patients with active uveitis. Taken together, our findings substantiate that downregulated miRNAs may play a crucial role in the pathogenesis of uveitis either in experimental animals or in human being.…”
Section: Discussionmentioning
confidence: 96%
“…VKH is an autoimmune disorder with meningismus, cerebrospinal fluid pleocytosis, auditory findings and integumentary findings. In a study to investigate the role of miRNAs in the pathogenesis of uveitis, miR-155, an immunologically relevant miRNA, was found to be expressed less in peripheral-blood mononuclear cells and dendritic cells of BD patients than of healthy controls [69]. No such difference was detected between VKH patients and healthy controls.…”
Section: Mirnas and Eye Disordersmentioning
confidence: 99%
“…In addition to TAB2, IL-6 and IL-1β were found to be the targets for miR-155. In contrast to the decreased expression of miR-155, TAB2 expression was found to be increased in BD patients with active uveitis when compared to healthy controls [69]. miR-155 expression is downregulated in the pathogenesis of BD but not in VKH.…”
Section: Mirnas and Eye Disordersmentioning
confidence: 99%
See 1 more Smart Citation